Effect of irrigation levels and methods on yield and water use efficiency of marigold (Tagetes erecta L.) (Indian Journal of Arid Horticulture, 2020)
The field experiment was conducted for consecutive two seasons during rabi 2017-18 and 2018-19 at Instructional Farm, College of Agriculture, S.K. Rajasthan Agricultural University, Bikaner (Rajasthan) to study the effect levels and methods of irrigation on yield and water use efficiency of marigold (Tagetes erecta L.). The experimental layout was carried out in randomized block design with four replications and treatments included three irrigation levels and three irrigation methods. Irrigation was given based on pan evaporation values following alternate day irrigation schedule for drip irrigation while, surface irrigation was given according to the locally adopted frequency. Results showed that IW/CPE ratio 1.0 recorded significantly higher flower yield (145.4 and 140.2 q ha'') in 2017-18 and 2018-19, respectively. Maximum water use (721.73 and 606.43 mm) was observed with same irrigation treatment in 2017-18 and 2018-19, respectively. Although, high water use efficiency (WUE) of 25.91 and 27.37 kg hamm was observed at IW/CPE ratio 0.6 in 2017-18 and 2018-19, respectively. Under different irrigation methods, maximum flower yield (150.6 and 144.6 q ha ̈1) and high WUE (26.43 and 29.31 kg ha'mm') was recorded under drip irrigation treatment in 2017-18 and 2018-19 respectively.
Keywords: Irrigation level; marigold; WUE; yield